Indoor Air Quality in UAE Office Buildings and Their Effects on occupants’ Health, Comfort, Productivity and Performance - Ibrahim, Hanan Ahmad (2015)
Indoor air quality has become one of the most important aspects that environmentalists, academics and even the general public is taking consideration on. Given the fact that humans spends majority of their daily hours indoors, good indoor air quality and comfort is of high criticality. In particular, Dubai has grown to be one of the busiest and fast-growing cities in the Middle East and in the world. With its population on continued rise, rapid urbanization and industrialization has consequences to the environment, especially to indoor air quality/environment. This research study aimed to explore and assess the various indoor air quality pollutants in office spaces in Dubai, and these pollutants might contribute to the negative health risks as well as the productivity of the occupants. It seeks to address some questions that guided the research study relating to the concentration levels of specific indoor air quality indicators (e.g. TVOC, Ozone, Carbon Monoxide, Carbon Dioxide, Relative Humidity and Temperature). The research study used convergent parallel design of mixed methodology, which includes conducting quantitative measurement of the concentration levels of the above-noted IAQ indicators and qualitative-oriented survey for occupants. The spot measurement phase was done in a total of 17 office spaces in Ajman University of Science and Technology. An indoor air quality monitoring instrument called Direct Sense-IAQ was used to measure the concentration levels of IAQ indicators for an 8-hour observation period. A survey was used to collect data from 80 occupants of these 17 office spaces. Findings showed that majority of the office spaces have average concentration levels of TVOC which are within the acceptable range of concentration based on international and Dubai building requirements and standards. Similarly, all monitored office spaces had average concentration levels of Carbon monoxide which were within the acceptable range set by ASHRAE and Dubai Building standards, as well as other international standards including NAAQS and WHO. Average concentration levels of ozone in all office spaces were lower than the standard values designated by international and local standards. Few office spaces have higher carbon dioxide concentration levels, which were above the acceptable concentration limit. The potential cause of this was the lack of open windows in these office spaces. Relative humidity and temperature levels at the office spaces were also within the acceptable range based on international and local standards for both the indicators.